Soursop leaf extract and fractions protects against L-NAME-induced hypertension and hyperlipidemia - Nsor, Okim Okim; Alabi, Babatunde Adebola; Badejo, Joseph Ayo; Afolabi, Faith; Nku-Ekpang, Okot-Asi; Iwalewa, Ezekiel Olugbenga (Frontiers in Nutrition, 2024)
Introduction: Despite the high phenolic content of Annona muricata, little is known about its antihypertensive and antihyperlipidemic properties. This study evaluated the anti-hypertensive and antihyperlipidemic potential of A. muricata leaf extracts.Materials and Methods: Forty-two (42) male Wistar rats were divided into seven groups of six (6) animals each. N-nitro-L-arginine methyl ester (L-NAME) was used to induce hypertension and hyperlipidemia.Results: Phytochemical screening of Annona muricata leaf extracts (AMLE) revealed the presence of saponins, alkaloids, flavonoids, tannins, coumarins, steroids, terpenoids, and phenols. Comparing the methanol extract with the ethyl acetate fraction, quantification revealed that the methanol extract contained more phenolics, flavonoids, and alkaloids. The AMLE rats significantly reduced triglycerides, total cholesterol, LDL, VLDL, atherogenic index, coronary risk index, and blood pressure. The significant decrease in GSH, catalase, SOD, GST, and oxidative stress markers (MDA, nitrites, and MPO) was reversed by AMLE in a dose-dependent manner. Also, the elevated serum levels of TNF-α and IL-1β in the hypertensive rats were attenuated in the treatment groups.Discussion: This study suggests the potential ameliorative effects of Annona muricata leaf extracts against L-NAME-induced hypertension in rats. Notably, the study showed the antioxidant and anti-inflammatory properties of A. muricata leaf extracts, which is seen in its ability to attenuate oxidative stress and inflammatory cytokines in L-NAME-induced hypertensive rats. A. muricata extracts also decreased atherogenic risk and improved lipid profiles.